The verbal system of Malay and Arabic: contrastive analysis - Ali, Asem Shehadeh Saleh (Center for Promoting Ideas (CPI), 2013)
This study examines the contrast between verbal system of Arabic and Malay. The researcher starts with a descriptive study for issues of verbal system in Mal’ay. The following subjects are discussed: active voice, passive voice, derivation through prefixes and suffixes, repetition of the numbers and structures. In Arabic this study describes conditional sentences, conjugation, the expression, actions in different kinds, derivation, inflection, types of sentences, derivation of verbs and forms of perfect. The study found that the differences between two languages are in the subject of present tense, future, verb agreement, and passive voice and active voice. Keywords: Contrastive Hypothesis - Malay- Arabic - Differences